2015
DOI: 10.1038/npp.2015.109
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Reserve Moderates Mesolimbic Responses to Opioids in a Humanized Mouse Model of the OPRM1 A118G Polymorphism

Abstract: The OPRM1 A118G polymorphism is the most widely studied μ-opioid receptor (MOR) variant. Although its involvement in acute alcohol effects is well characterized, less is known about the extent to which it alters responses to opioids. Prior work has shown that both electrophysiological and analgesic responses to morphine but not to fentanyl are moderated by OPRM1 A118G variation, but the mechanism behind this dissociation is not known. Here we found that humanized mice carrying the 118GG allele (h/mOPRM1-118GG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Conversely, in HEK239 cells, no effect of genotype was observed on suppression of Ca 2+ channel inhibition following BPN administration (Robinson et al, 2015). These contradictory findings may be a result of cell specific differences in Gα and βγ subunits, that mask genotype dependent changes in BPN mediated second messenger coupling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in HEK239 cells, no effect of genotype was observed on suppression of Ca 2+ channel inhibition following BPN administration (Robinson et al, 2015). These contradictory findings may be a result of cell specific differences in Gα and βγ subunits, that mask genotype dependent changes in BPN mediated second messenger coupling.…”
Section: Discussionmentioning
confidence: 99%
“…In a complimentary approach, a different mouse line was generated that express humanized receptors with and without the A118G variant (Ramchandani et al, 2011). The effects of morphine but not fentanyl on intracranial self-stimulation and dopamine release in the nucleus accumbens were blunted in the humanized mouse model of the OPRM1 A118G polymorphism (Robinson et al, 2015). Using the same model, trigeminal ganglion neurons isolated from mice with the G allele exhibited blunted inhibition of Ca 2+ channels following morphine but not fentanyl administration ex vivo (Mahmoud et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation for the decreased morphine sensitivity in 118GG mice is that the G allele causes decreased amounts of MOR protein. Previous reports showing that the G allele causes decreased MOR mRNA expression, protein levels, and/or protein stability support this possibility (Zhang et al, 2005; Mague et al, 2009; Huang et al, 2012; Wang et al, 2012; Wang et al, 2014; Robinson et al, 2015). …”
Section: 1 Discussionmentioning
confidence: 82%
“…The use of different genetic models (humanized vs. mouse transgenic) might be responsible for the slight discrepancies between these two studies. However, Robinson and colleagues recently found that humanized male 118GG mice display less morphine-stimulated dopamine release in the nucleus accumbens and decreased morphine reward [assessed using an intra-cranial self-stimulation (ICSS) model] compared to 118AA controls (Robinson et al, 2015). Despite the reduction in dopamine release and morphine reward, transgenic 112GG mice self-administer more heroin than 112AA mice (Zhang et al, 2015).…”
Section: 1 Discussionmentioning
confidence: 99%
“…A loss of function in the minor allele caused differential outcomes, which might account for the different reward behaviors induced by drugs of abuse ( Fig. 1A) (Ramchandani et al, 2011;Bilbao et al, 2015;Robinson et al, 2015;Zhang et al, 2015;Browne et al, 2017) or other types of behavior (Briand et al, 2015).…”
Section: Impact Of Oprm1 A118 Gene Variant (N40d Mors) On Synaptic Rementioning
confidence: 99%